Development of non-contact liquid level measurement and data storage system - Rashid, Muhammad Mahbubur; Al Mamun, Abdullah; Jaafar, Abdul Hassan; Mollik, Md. Sajib (International Journal of Engineering Materials and Manufacture, 2018)
The normal contact type liquid measurement devices have some drawbacks since they have potential damage due to the sensor fouling or corrosion since those are continuously exposed to the liquid. Especially flash flood may cause the damage of liquid level sensor. So that, it is important to design a non-contact device for liquid level measurement in order to avoid this constrain. Distance can be measured without contact such as laser, ultrasonic and radar. In this research, ultrasonic sensor is used to provide non-contact feature of the device since it is low cost and uses ultra-sound waves rather than light. This vital sensing device is able to sense uneven surfaces, liquids, clear objects, and objects in dirty environments. This paper discussed the measurement of liquid level in a tank as well as storing historical data.